Exploiting multipath propagation for GMTI in urban environments - Krolik, J.L.; Farrell, J.; Steinhardt, A. (2006 IEEE Conference on Radar, 2006)
This paper evaluates the potential for exploiting multipath propagation for improved radar detection of moving ground targets in dense urban environments. In particular, the radar coverage offered by exploiting non-line-of-sight (NLOS) propagation from an airborne radar platform is considered. A quasi-analytical model for NLOS propagation assuming multiple specular reflections off buildings is derived to evaluate radar coverage as a function of target range, aircraft altitude, building height and separation, and relative target position on a street. A statistical characterization of the urban environment is used to compute probabilities of line-of-sight versus non-line-of-sight propagation and surveillance sweep width. Comparison of sweep width for LOS versus at least one NLOS path indicates that NLOS could offer a significant improvement in coverage rate. In essence, NLOS propagation permits radar surveillance at longer ranges with lower altitude radar platforms. In addition to radar coverage, the Cramer-Rao lower bound (CRLB) for estimation of target position in a specular multipath environment is derived. The CRLB indicates that, in theory, range accuracy improves with multiple paths and that only three paths are required to jointly estimate target range, position within the street, and street width.